Exploring the nexus between procurement contract administration and quality attainment of force account construction projects in Tanzania - Shadrack Samwel Mwaiseje; Alban Dismas Mchopa; Faustine Peter Panga; Mathias Sylvester Nkuhi (Cogent Engineering)
Currently, there is an increasing focus on procurement contract administration as among of the key variables in explaining the performance of construction projects. Despite such observations, their relationship with quality attainment of the Force Account (FA) construction projects is not well postulated to cement the observed causal relationship. Therefore, this study assesses the role of procurement contract administration in the quality attainment of FA construction projects in Local Government Authorities (LGAs) in Tanzania. The study employed a cross-sectional research design, and data was collected by using structured questionnaires from primary schools in Dodoma, Tanzania. The study used 318 respondents to analyse data by using Partial least square structural equitation modelling (PLS-SEM). The findings of the study reveal that risk management, relationship management, dispute management, and monitoring and control are positive and significant factors in explaining the quality attainment of FA construction projects. Notably, risk management is the strongest predictor of quality attainment of FA construction projects. It was concluded that the quality attainment of FA construction projects is highly influenced by procurement contract administration. These findings have practical implications, as procurement practitioners and FA committees can use them to make decisions concerning the quality attainment of the projects through the implementation of procurement contract administration practices.